PENCEGAHAN TERBENTUK NYA PRODUK SCALE PADA PIPA PRODUKSI AREA MINAS DENGAN INJEKSI CHEMICAL SCALE INHIBITOR - MUSMULIADI (Fakultas Teknik UMRI, 2020)
Scale is a collection of deposits that become crusted and can cover holes, production tubes and valves so as to block the flow of fluid. Scale can reduce the diameter of the production pipe and cause the fluid flow to decrease so that the amount of production is reduced. In addition, the existence of a scale can cause an increase in pressure in the pipe, if the scale is too large it can cause the production pipe to burst. For that we need treatment for the scale case that occurs, how to overcome and reduce the possibility of scale formation on the inside of the pipe. In the production facility, problems that can interfere with the distribution of crude oil (crude oil) are often encountered. This is generally caused by the formation of deposits (scale) along the distribution pipe. Scale is a solid (crust) resulting from crystallization and deposition of mineral formations with bacteria produced together with oil and gas. The scale formation is predicted because the bacteria contained in petroleum are attached to the distribution pipe to form crystal clumps.